Randomized phase 2 study of otlertuzumab and bendamustine versus bendamustine in patients with relapsed chronic lymphocytic leukaemia. (15th December 2016) - Robak, Tadeusz; Hellmann, Andrzej; Kloczko, Janusz; Loscertales, Javier; Lech‐Maranda, Ewa; Pagel, John M.; Mato, Anthony; Byrd, John C.; Awan, Farrukh T.; Hebart, Holger; Garcia‐Marco, Jose A.; Hill, Brian T.; et al.
Summary: Otlertuzumab (TRU‐016) is a humanized anti‐CD37 protein therapeutic that triggers direct caspase‐independent apoptosis of malignant B cells and induces antibody‐dependent cell‐mediated cytotoxicity. Patients with relapsed chronic lymphocytic leukaemia (CLL) received either otlertuzumab (20 mg/kg) weekly by IV infusion for two 28‐day cycles then every 14 days for four 28‐day cycles and IV bendamustine (70 mg/m 2 ) on Days 1 and 2 of each cycle for up to six 28‐day cycles or bendamustine alone. Thirty‐two patients were treated with otlertuzumab and bendamustine and 33 with bendamustine alone. Overall response rate according to the International Workshop on Chronic Lymphocytic Leukaemia criteria was 69% in the otlertuzumab and bendamustine arm and 39% in the bendamustine alone arm ( P = 0·025). Median progression‐free survival (PFS) was 15·9 months in the otlertuzumab and bendamustine arm and 10·2 months in the bendamustine alone arm ( P = 0·0192). There was a higher incidence of pyrexia (34% vs. 12%) and neutropenia (59% vs. 39%) with the combination but this did not result in a higher incidence of severe (grade 3/4) infections (13% vs. 27%). This combination significantly increased the response rate and prolonged the PFS over single agent bendamustine in patients with relapsed or refractory CLL.